Innovative Lightweight Concrete Incorporating Pumice Stone and Palm Oil Fuel Ash - RIDZUAN, MUHAMMAD IMRAN; OSMAN, MOHAMAD HAIRI (Progress in Engineering Application and Technology, 2025)
The increasing demand for sustainable building materials has driven the development of innovative alternatives to traditional concrete. This study explores the incorporation of Pumice Stone (PS) and Palm Oil Fuel Ash (POFA) in the production of lightweight concrete. PS, a natural lightweight aggregate, replaces conventional coarse aggregate, while POFA, a byproduct from palm oil mills, serves as a partial cement replacement due to its pozzolanic properties. A total of 48 concrete specimens were prepared using a Department of Environment (DOE) mix design, varying POFA content at 0%, 10%, 20%, and 30% by cement weight. Compressive strength ASTM C39, split tensile strength ASTM C496, and water absorption ASTM C642 tests were conducted at 7 and 28 days. The results revealed that a 20% POFA replacement yielded optimal mechanical performance, lower density, and acceptable water absorption. This confirms the viability of using PS and POFA to produce environmentally friendly, structurally efficient lightweight concrete.